Dietary supplementation with sodium humate improves egg quality and immune function of laying hens - A.R. Zhang; S.A. Pirzado; G.H. Liu; Z.M. Chen; W.H. Chang; H.Y. Cai; W.L. Bryden; A.J. Zheng (Journal of Applied Animal Nutrition)
The aim of this study was to evaluate the influence of the dietary addition of sodium humate (HAS) on performance and immune response of laying hens during peak lay, over an eight-week period. Laying hens, aged 24 weeks old, were randomly allotted to four dietary treatments: a basal control diet or the basal diet supplemented with 0.1, 0.3 or 0.5% HAS. Each treatment had six replicates with 15 layers per replicate. Egg production, egg quality, serum antioxidant parameters and immunity indexes were measured. HAS had no significant effect on egg production or egg and shell quality, but all supplemental levels significantly improved Haugh unit values and egg yolk colour. Supplementation with all levels of HAS significantly increased serum immunoglobuline (Ig) level compared to the hens fed the control diet. Feeding either 0.1 or 0.5% HAS significantly increased serum IgM levels. The results indicated that dietary supplementation with HAS can enhance egg albumin quality and improve immunity in laying hens.